Bioactive Compound Profiling of Ethyl Acetate Fraction from Oil Palm (Elaeis guineensis Jacq.) Leaves using Liquid Chromatography High Resolution Mass Spectrometry (LC-HRMS) - Deni Setiawan; Samsul Hadi; Nur Mahdi; Nurul Mardiati; Normaidah; Nabila Hadiah Akbar; Muhammad Rasyid Ridha; Fitri Apriliany (Sinteza, 2025)
Oil palm leaves could yield various health benefits, potentially leading to innovative applications in natural remedies, supplements, and dietary products. Targeted extraction and sophisticated analytical methods have become necessary for investigating bioactive compounds in plant materials. The combination of liquid chromatography and high-resolution mass spectrometry (LC–HRMS) makes for a potent technique for analyzing a wide range of metabolites, allowing for the precise and sensitive identification of various plant compounds. This investigation aimed to examine the active compounds in the ethyl acetate fraction of Elaeis guineensis leaves using LC–HRMS to identify potential new avenues for drug research. The simplicia was extracted by completely immersing 500 g of granules in acetone for three days. The crude extract was fractionated with n-hexane, ethyl acetate, and n-butanol solvents to separate components according to their polarity. The ethyl acetate part was analyzed using LC–HRMS with specific settings, including a temperature of 30°C and a gas flow rate of 11.01 L/min. The extract yield from dense oil palm leaves was 32.5 g, equivalent to 6.5%. Subsequently, the components were separated by fractionating the complete yield. The n-hexane fraction yield was 7.085 g or 21.83%, the ethyl acetate fraction yield was 3.38 g or 10.4%, the n-butanol fraction yield was 8.84 g or 27.2%, and the remaining fraction yield was 3.93 g or 12.1%. In conclusion, oil palm leaves are a prospective source of zingerol compounds, suggesting potential to be used as an alternative to rhizomes.